Review of the experimental and theoretical landscape of electron transport in noble liquids - Boyle, G. J.; Garland , N. A.; Muccignat , D. L.; Simonović , I.; Bošnjaković , D.; Dujko , S.; White , R. D. (Frontiers in Detector Science and Technology, 2025)
We present a review of the current experimental and theoretical understanding of electron transport in noble liquids. Special attention is given to recent measurements that coincide with the development of time projection chambers using liquid xenon and argon as detector media. To enable transparent benchmarking of simulations and to facilitate the comparison between early studies and modern time projection chamber data, we introduce a new open-access database of electron mobility and diffusion measurements. In particular, we emphasize the transition to large-scale detector designs which incorporate extended drift distances alongside improved purity control and field uniformity. On the theoretical side, we contrast empirical transport models with ab initio approaches, highlighting our recent efforts to incorporate low-energy, liquid-specific scattering phenomena, including coherent scattering, polarization screening, and bulk potential modifications. While elastic transport has seen substantial theoretical progress, inelastic processes in liquids, including ionization, exciton formation and interband transitions, remain poorly understood due to the lack of experimental cross sections and validated models. We also discuss the applications and challenges of modeling scintillation, doped and mixture-liquid targets, and gas–liquid interface behavior, all of which are critical for the design and optimization of next-generation detectors.